2012
DOI: 10.5588/ijtld.11.0183
|View full text |Cite
|
Sign up to set email alerts
|

Quitting smoking with varenicline: parallel, randomised efficacy trial in Iran

Abstract: In the study, varenicline treatment was slightly more effective than but not significantly different from nicotine replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 0 publications
3
46
1
5
Order By: Relevance
“…After the removal of duplicates and screening of titles and abstracts, 68 trials underwent full‐text review. In total, 38 RCTs met all eligibility criteria and were included in our meta‐analysis 10, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49…”
Section: Resultsmentioning
confidence: 99%
“…After the removal of duplicates and screening of titles and abstracts, 68 trials underwent full‐text review. In total, 38 RCTs met all eligibility criteria and were included in our meta‐analysis 10, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49…”
Section: Resultsmentioning
confidence: 99%
“…any formulations such as gums, spray and/or patches) although variations in population characteristics or clinical practice appear to influence the effectiveness of both therapies (Brose, West, & Stapleton, 2013). A randomized parallel clinical trial in 272 subjects reported equivalent success between varenicline and nicotine patches at 1, 6 and 12 months of follow-up (Heydari, Talischi, Tafti, & Masjedi, 2012), while a meta-analysis concluded that varenicline and combined NRT were equally effective in continuous or prolonged abstinence during at least 6 months (Cahill, Stevens, Perera, & Lancaster, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Three papers were included from the updated search. [37][38][39] All three papers measured smoking cessation rates by PPA. The study reported in Cahill et al 15 as Pfizer 2011 40 was identified in the updated search as now being a published paper.…”
Section: Updated Searchmentioning
confidence: 99%
“…[37][38][39] All three studies were single-country studies, carried out in Canada, the USA, and Iran respectively. Wong et al 37 conducted the study at two sites -both pre-operative clinics in hospitals in Canada.…”
Section: Description Of Studies From Updated Searchmentioning
confidence: 99%
See 1 more Smart Citation